Effect of the Coating Formulation on the Barrier Properties and Final Appearance of Non-wettable Hybrid Paper Sheets - ÖZOMAY, ZAFER; UZUN, MUHAMMET; SÖNMEZ, SİNAN (My University, 2024)
Thin coating layers of cross-linked polydimethylsiloxane (PDMS) and inorganic particles including glass spheres (GS), colloidal and fumed silica (aero and N20), montmorillonite (MMT), and kaolin (K) were attached onto Grade 1 Whatman filter paper (WFP) substrates using the spraycoating procedure to achieve superhydrophobic hybrid paper sheets. Coating formulations were varied in terms of their PDMS molecular masses and inorganic particles to prepare different samples. The effect of PDMS molecular weight and change in inorganic particle composition on the optical properties, surface roughness, barrier properties, surface chemistry, and topography was investigated. Hybrid paper sheets with ΔE00 values lower than 1 could be achieved, the surface roughness of which could be decreased by increasing the PDMS molecular weight in the coating formulation. Scanning electron microscopy studies revealed a homogeneous coating distribution, resulting in significant improvements in both the air and water barrier properties of the hybrid paper sheets. Spectroscopic investigations revealed the presence of interactions between the coating layer and the underlying paper substrate. Moreover, the distribution behavior of the inorganic particles on the spraycoated surfaces using the proposed method was also investigated using model compounds.
Keywords: Kimya; Fizikokimya; Diğer; Temel Bilimler; Chemistry; Physical Chemistry; Other; Natural Sciences; Temel Bilimler (SCI); KİMYA, UYGULAMALI; KİMYA, FİZİKSEL; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, APPLIED; CHEMISTRY, PHYSICAL; Proses Kimyası ve Teknolojisi; Fizik Bilimleri; Yüzeyler, Kaplamalar ve Filmler; Process Chemistry and Technology; Physical Sciences; Surfaces, Coatings and Films; Cellulose; Coating; Packaging; Paper; Superhydrophobic